Mark B. Whitaker Water Treatment Plant: Maintaining History With Modern Advancements. Issue 7 (1st July 2016) - May, Andrea; Lane, Kelly; Thomas, Chris; Bolanos, Santiago
Abstract : WITHIN THE STATELY BRICK EXTERIOR OF THE 1927 MARK B. WHITAKER WATER TREATMENT PLANT ARE STATE‐OF‐THE‐ART EQUIPMENT AND PROCESSES THAT PROVIDE HIGH‐QUALITY WATER TO EAST TENNESSEE.